A study on training factors and its impact on training effectiveness in Kedah State Development Corporation, Kedah, Malaysia - Sanjeevkumar, Virmala; Hu, Yanan (Macrothink Institute, 2011)
In Malaysia so many enterprise implement various training program to enhance their employees by working performance. But as overall view, the training environment still exist shortages in enterprise today, for instance, lack of knowledge of training, resources, trainer etc..Employee training has been a matter of concern and attention by many business fields nowadays.Organizations realize that employee training is an essential element to increase efficiency of job performance and keep their business running, as competition are getting more intense.Training is the process of providing employees with specific skills or helping research also determine the main factors which influence employee training on human resource practices.Management is committed to human resource development as well as its social responsibilities through various programs. Training and development programs are offered by the KSDC Company that training program also adapted to the latest technological advances.